Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/anie.200802564
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chiral and Racemic Forms of Zinc Cyclohexane trans‐1,2‐Dicarboxylate Frameworks: A Structural, Computational, and Calorimetric Study

Abstract: An integrated study of the organic–inorganic framework material zinc cyclohexane trans‐1,2‐dicarboxylate involving synthesis, structure elucidation, computer simulation, and calorimetry shows that the chiral R,R form (right in picture) is less stable than its racemic R,R/S,S analogue (left) and adopts a layered structure with a fundamentally different topology. The results point to the possibility that the structural diversity of racemic frameworks and their homochiral analogues may be much greater than has hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Conversely, the racemic mixture, [Cu(R,S-valmet) (H 2 O) 2 ], in the reaction with HgCl 2 and HgI 2 , leads to centrosymmetric discrete trinuclear, respectively, tetranuclear complexes. The results we have presented herein, together with several papers published by others, [13][14][15][16] illustrate that the structures of complexes assembled from enantiopure ligands/metalloligands are different from those resulting when the racemic mixture is employed.…”
Section: Discussionmentioning
confidence: 50%
“…Conversely, the racemic mixture, [Cu(R,S-valmet) (H 2 O) 2 ], in the reaction with HgCl 2 and HgI 2 , leads to centrosymmetric discrete trinuclear, respectively, tetranuclear complexes. The results we have presented herein, together with several papers published by others, [13][14][15][16] illustrate that the structures of complexes assembled from enantiopure ligands/metalloligands are different from those resulting when the racemic mixture is employed.…”
Section: Discussionmentioning
confidence: 50%
“…[59] In a further study, the possibility of using R,R-and S,Senantiomers of trans-1,2-dicarboxylate was also investigated, combining synthesis, calorimetry, and computational approaches. [60] The obtained racemic R,R-S,Sand chiral R,R-Zn-dicarboxylates possess fundamentally different topologies (Figure 9), the first being constructed from four rings and the second of three rings of tetrahedrally coordinated zinc ions. Using this time, the force field developed for Zn-based MOFs by Allendorf et al [61] we showed that the less dense racemic R,R-S,SZn-dicarboxylate structure is more stable than the chiral R, R-dicarboxylate phase, in excellent agreement with the calorimetric estimations of differences of enthalpies of solution for both compounds.…”
Section: Chiral Mofs Versus Non Chiral Mofsmentioning
confidence: 99%
“…The dense chiral (left) and less dense racemic (right) structures (bottom). Illustration adapted from[60].…”
mentioning
confidence: 99%
“…Cheetham and his co-workers explored the racemic and homochiral forms of zinc cyclohexane-trans-1,2-dicarboxylate, [Zn(trans-12-CDA)] using R,R/S,S-12-CDA and its enantiomeric R,Ranalogue [22]. Both compounds are layered 2-D coordination polymers, comprising double rows of ZnO 4 tetrahedra with pendant cyclohexane rings decorating both sides of the layers, giving rise to non-covalent interlayer interactions (Fig.…”
Section: Coordination Compounds Based On 12-cyclohexanedicarboxylatementioning
confidence: 99%